Association between lower frequency of R381Q variant (rs11209026) in IL-23 receptor gene and increased risk of recurrent spontaneous abortion (RSA). (October 2015) - Abdollahi, Elham; Tavasolian, Fataneh; Ghasemi, Nasrin; Mirghanizadeh, Seyed Ali; Azizi, Mohammdareza; Ghoryani, Mohsen; Samadi, Morteza
Abstract Recurrent spontaneous abortion (RSA) is defined as three or more consecutive spontaneous abortions before the 20th week of gestation. The purpose of the present study was to investigate the association between a functional single nucleotide polymorphism (SNP) in the interleukin (IL)-23 receptor gene (IL-23R; rs11209026, 1142 G wild type → A reduced function, Arg381Gln, R381Q) and RSA. For the study, 200 RSA patients (confirmed using established diagnostic criteria) and 200 normal individuals in fertility and infertility centers in the cities of Yazd and Isfahan were recruited during a period from 2012–2013. Using PCR-RFLP, the R381Q variant was screened for in the IL-23R gene of the patients and controls. The results indicated there were significant differences in the frequency of this genetic variant in the patients versus the healthy controls, i.e. 2% and 7.5%, respectively (p value = 0.01; odds ratio = 0.25; CI = 95%). No significant difference was found for the G allelic frequency in patients with RSA and in the control group (p = 0.60). The A allelic frequency was significantly different between the two groups (p = 0.01). Based on these findings, it is concluded that the frequency of single nucleotide polymorphism in the IL-23 receptor (R381Q) in patients with recurrent spontaneous abortion (RSA) is less than that found in normal control women.